2021
DOI: 10.1002/cnr2.1390
|View full text |Cite
|
Sign up to set email alerts
|

The importance of time‐to‐adjuvant treatment on survival with pancreatic cancer: A systematic review and meta‐analysis

Abstract: Background: While adjuvant chemotherapy benefits patients with pancreatic ductal adenocarcinoma (PDAC), the importance of the time to initiation of adjuvant therapy remains unclear.Aim: This study seeks to better understand whether the timing of postoperative chemotherapy initiation affects long-term outcomes in PDAC. Methods and Results: A systematic literature search was performed in Medline, Embase, and Cochrane Library in March 2020. Studies focused on the association between the timing of adjuvant therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Investigations focused on the timing of adjuvant chemotherapy in PC have produced mixed results. A meta-analysis concluded that commencing adjuvant therapy within 20 days after surgery was correlated with improved overall survival [11]. However, the ESPAC-3 study found no notable outcome difference when adjuvant chemotherapy was delayed by up to 12 weeks to allow for postoperative recovery [12].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations focused on the timing of adjuvant chemotherapy in PC have produced mixed results. A meta-analysis concluded that commencing adjuvant therapy within 20 days after surgery was correlated with improved overall survival [11]. However, the ESPAC-3 study found no notable outcome difference when adjuvant chemotherapy was delayed by up to 12 weeks to allow for postoperative recovery [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although some data suggest that the early initiation of adjuvant chemotherapy might be associated with longer survival, 42 , 43 most data support that there is no to minimum difference in outcomes based on the time to initiate chemotherapy. 44 Data from the ESPAC-3 trial have not shown improved survival for patients starting adjuvant chemotherapy within 8 weeks of surgery (vs 8–12 weeks). 40 Additionally, multiple analyses suggest that the benefit of adjuvant chemotherapy stands even for patients who start chemotherapy after 12 weeks.…”
Section: Adjuvant Therapymentioning
confidence: 99%